12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23

Simple and best practice solution for 12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23 equation:


Simplifying
12(7X + -1) + -8(6X + 1) + (5X + 3) * 11 = 23(4X + -1X) + 23

Reorder the terms:
12(-1 + 7X) + -8(6X + 1) + (5X + 3) * 11 = 23(4X + -1X) + 23
(-1 * 12 + 7X * 12) + -8(6X + 1) + (5X + 3) * 11 = 23(4X + -1X) + 23
(-12 + 84X) + -8(6X + 1) + (5X + 3) * 11 = 23(4X + -1X) + 23

Reorder the terms:
-12 + 84X + -8(1 + 6X) + (5X + 3) * 11 = 23(4X + -1X) + 23
-12 + 84X + (1 * -8 + 6X * -8) + (5X + 3) * 11 = 23(4X + -1X) + 23
-12 + 84X + (-8 + -48X) + (5X + 3) * 11 = 23(4X + -1X) + 23

Reorder the terms:
-12 + 84X + -8 + -48X + (3 + 5X) * 11 = 23(4X + -1X) + 23

Reorder the terms for easier multiplication:
-12 + 84X + -8 + -48X + 11(3 + 5X) = 23(4X + -1X) + 23
-12 + 84X + -8 + -48X + (3 * 11 + 5X * 11) = 23(4X + -1X) + 23
-12 + 84X + -8 + -48X + (33 + 55X) = 23(4X + -1X) + 23

Reorder the terms:
-12 + -8 + 33 + 84X + -48X + 55X = 23(4X + -1X) + 23

Combine like terms: -12 + -8 = -20
-20 + 33 + 84X + -48X + 55X = 23(4X + -1X) + 23

Combine like terms: -20 + 33 = 13
13 + 84X + -48X + 55X = 23(4X + -1X) + 23

Combine like terms: 84X + -48X = 36X
13 + 36X + 55X = 23(4X + -1X) + 23

Combine like terms: 36X + 55X = 91X
13 + 91X = 23(4X + -1X) + 23

Combine like terms: 4X + -1X = 3X
13 + 91X = 23(3X) + 23

Remove parenthesis around (3X)
13 + 91X = 23 * 3X + 23

Multiply 23 * 3
13 + 91X = 69X + 23

Reorder the terms:
13 + 91X = 23 + 69X

Solving
13 + 91X = 23 + 69X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-69X' to each side of the equation.
13 + 91X + -69X = 23 + 69X + -69X

Combine like terms: 91X + -69X = 22X
13 + 22X = 23 + 69X + -69X

Combine like terms: 69X + -69X = 0
13 + 22X = 23 + 0
13 + 22X = 23

Add '-13' to each side of the equation.
13 + -13 + 22X = 23 + -13

Combine like terms: 13 + -13 = 0
0 + 22X = 23 + -13
22X = 23 + -13

Combine like terms: 23 + -13 = 10
22X = 10

Divide each side by '22'.
X = 0.4545454545

Simplifying
X = 0.4545454545

See similar equations:

| -1x+12-3x=-5(x-2)+1 | | 2+3x=5x+24 | | 5/2=17/3 | | 3x+7x=850 | | 0=ln(x^2+5)+0.5x+1 | | -2x+12-2x=-5(x-1)+2 | | -2x+12-2x=-5(x-2)+2 | | 3x+5x=850 | | 12+10=14y-3y | | -2x+10-3x=-5(x-2)+2 | | 8-6x-3=-21+4x-14 | | 7(x+2)=9x+2 | | 2(1x+8)=12 | | 6x^2-12=5x^2-4x | | X/12=34 | | -1x+12-3x=-5(x-2)+2 | | 18y^2-7y-2=0 | | 4x-x+9=(x+2)+p | | g(-1)forg(t)=(t^2-1)(t+4) | | 4n-2=4n-6 | | -2x+11-3x=-5(x-2)+2 | | 4+77x=44x+16 | | X-(-8)=15.6 | | 2x+6=-22-5x | | -2x+12-3x=-5(x-2)+2 | | 5(-3+6x)=-15 | | -1/3-g=-1/3 | | 8w-17w=18 | | 3e^2x+5=15 | | 10m+6=76 | | X-(5x+2)=2 | | 36a^2+120a+64=0 |

Equations solver categories